Adaptation and Cryptic Pseudogenization in Penguin Toll-Like Receptors. (13th December 2021) - Fiddaman, Steven R; Vinkler, Michal; Spiro, Simon G; Levy, Hila; Emerling, Christopher A; Boyd, Amy C; Dimopoulos, Evangelos A; Vianna, Juliana A; Cole, Theresa L; Pan, Hailin; Fang, Miaoquan; Zhang, Guojie; et al.
Abstract: Penguins (Sphenisciformes) are an iconic order of flightless, diving seabirds distributed across a large latitudinal range in the Southern Hemisphere. The extensive area over which penguins are endemic is likely to have fostered variation in pathogen pressure, which in turn will have imposed differential selective pressures on the penguin immune system. At the front line of pathogen detection and response, the Toll-like receptors (TLRs) provide insight into host evolution in the face of microbial challenge. TLRs respond to conserved pathogen-associated molecular patterns and are frequently found to be under positive selection, despite retaining specificity for defined agonist classes. We undertook a comparative immunogenetics analysis of TLRs for all penguin species and found evidence of adaptive evolution that was largely restricted to the cell surface-expressed TLRs, with evidence of positive selection at, or near, key agonist-binding sites in TLR1B, TLR4, and TLR5 . Intriguingly, TLR15, which is activated by fungal products, appeared to have been pseudogenized multiple times in the Eudyptes spp., but a full-length form was present as a rare haplotype at the population level. However, in vitro analysis revealed that even the full-length form of Eudyptes TLR15 was nonfunctional, indicating an ancestral cryptic pseudogenization prior to its eventual disruption multiple times in the Eudyptes lineage. This unusual pseudogenization event could provide an insight into immune adaptation to fungal pathogens such as Aspergillus, which is responsible for significant mortality in wild and captive bird populations.